Kristallstruktur eines N-Acetyl-α-cyclopropalanyl-phenylalanin-dimethylamids; Konfigurationsbestimmung der α,α-disubstituierten Aminosäure - Friedrich Stierli; Roland Prewo; Jost H. Bieri; Heinz Heimgartner (CHIMIA)
The structure and configuration of N-acetyl-(S)-α-cyclopropyl-alanyl-(S)-phenylalanin-dimethylamid (3’), prepared by condensation of racemic N-acetyl-α-cyclopropylalanin (1) and (S)-phenylalanin-dimethylamide (2, Scheme 1) and separation of the diastereomers, have been determined by X-ray crystallography.